2005
DOI: 10.1016/j.jacc.2004.12.083
|View full text |Cite
|
Sign up to set email alerts
|

Guideline-Based Standardized Care Is Associated With Substantially Lower Mortality in Medicare Patients With Acute Myocardial Infarction

Abstract: Embedding AMI guidelines into practice was associated with improved 30-day and one-year mortality. This benefit is most marked when patients are cared for using standardized, evidence-based clinical care tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
8

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 225 publications
(65 citation statements)
references
References 33 publications
2
55
0
8
Order By: Relevance
“…In the QUICC hospitals 2.8 lives per 100 patient years (14.2 to 11.4) and 9.3 readmissions for cardiac diagnoses per 100 patient years (49.5 to 40.2) were saved after compared to before the QI intervention, corresponding to a 20% and 19% relative decrease in incidence, respectively. The magnitude of improvement in clinical outcome was in the same order as in the study of Lappe et al, 23 in which the 21% decrease in 1-year mortality was seen and in the Guidelines Applied in Practice project in which a 22% decrease in 1-year mortality 8 and a 21% decrease in 6-months rehospitalization rates 24 were shown. It is most probable that the improvement in clinical outcome in the QUICC hospitals was a result of the increase in the use of evidence-based treatments, and that the lack of significant improvement in the control hospitals was attribtuable to the much smaller increase in use of these The values represent the median hospital in each group.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the QUICC hospitals 2.8 lives per 100 patient years (14.2 to 11.4) and 9.3 readmissions for cardiac diagnoses per 100 patient years (49.5 to 40.2) were saved after compared to before the QI intervention, corresponding to a 20% and 19% relative decrease in incidence, respectively. The magnitude of improvement in clinical outcome was in the same order as in the study of Lappe et al, 23 in which the 21% decrease in 1-year mortality was seen and in the Guidelines Applied in Practice project in which a 22% decrease in 1-year mortality 8 and a 21% decrease in 6-months rehospitalization rates 24 were shown. It is most probable that the improvement in clinical outcome in the QUICC hospitals was a result of the increase in the use of evidence-based treatments, and that the lack of significant improvement in the control hospitals was attribtuable to the much smaller increase in use of these The values represent the median hospital in each group.…”
Section: Discussionsupporting
confidence: 68%
“…10 -12 The results from these studies have been varying, from modest [21][22] to more substantial. 8 Unfortunately, these studies did not include comparisons with concurrent control groups, which made it arguable whether the results primarily were an effect of the QI interventions per se, or maybe mere expressions of secular trends in AMI care.…”
mentioning
confidence: 99%
“…Previous studies showing the benefit EBM in unselected patients had a follow-up period of 6 months [1] to a year [2,9], and most studies summed the number of EBM medications used (aspirin, beta-blockers, statins, ACEinhibitors/angiotensin receptor blockers) assuming that different EBM medications are "equivalent" in providing prognostic benefit. Our study with an up to 5 years follow-up showed that patients prescribed aspirin likely had benefited to different extents from the 3 other EBM medications.…”
Section: Discussionmentioning
confidence: 99%
“…In the Guideline Applied in Practice (GAP) Projects, a comparison of 2 cohorts of patients with acute myocardial infarction (including 1368 patients in the year before and 1489 patients in the first 4 months of GAP implementation) revealed that GAP implementation resulted in higher use of EBM medications and lower mortality up to 1 year [2].…”
Section: Introductionmentioning
confidence: 99%
“…Successful tool use is critical because, as demonstrated in previous projects, when the AMI specific tools are used (Fig. 2), rates for quality of care measures are high (8,9), and there is a corresponding improvement in 30-day and 1-year outcomes (Tables 1, 2, and 3) (13). Physician champions and project leaders subsequently coordinated multidisciplinary teams to plan their respective hospital's activities.…”
Section: Acc Ami-gap Qi Modelmentioning
confidence: 96%